Authentic Indians episodes of encounter from the late-nineteenth-century Northwest coast - Raibmon, Paige Sylvia 1971- (Duke University Press, 2005)
Introduction: authenticity and colonial cosmology -- Local politics and colonial relations : the Kwakwaka'wakw at home on the Northwest coast -- "The march of the aborigine to civilization" : live exhibits and the world's Columbian exposition, 1893 -- Theaters of contact : the Kwakwaka'wakw at the fair -- Picking, posing, and performing : the hop fields and income for aboriginal workers -- Harvest gatherings : aboriginal agendas, economy, and culture -- Indian watchers : colonial imagination and colonial reality -- The inside passage to authenticity : Sitka tourism and the Tlingit -- "The trend is upward" : mission and cottage life -- Civilization on trial : the Davis case -- Conclusion: authenticity's call